Enhancing quality of life in head and neck cancer patients: a comparative analysis of 3D exoscope-assisted surgery vs. traditional approaches - Marchi, Filippo; Bellini, Elisa; Ioppi, Alessandro; Simoni, Federica; Iandelli, Andrea; Filauro, Marta; Mora, Francesco; Sampieri, Claudio; Peretti, Giorgio (Frontiers in Surgery, 2024)
The increasing population of survivors of head and neck carcinomas is becoming more conspicuous.Consequently, the pivotal role of quality of life, particularly elucidated through the assessment of dysphagia and dysphonia, is progressively influencing the decision-making process. The current study aims to assess whether VITOM 3D could offer a comparable post-treatment quality of life to traditional approaches for patients with laryngeal cancer and oro-hypopharyngeal cancer.A case series of laryngeal cancer and oro-hypopharyngeal cancer patients treated either with an exoscopicassisted surgical setup and with conventional treatments (transoral microsurgery and radio-chemotherapy) at